2006
DOI: 10.1287/isre.1060.0088
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Adoption of Multipurpose Information Appliances: The Case of Mobile Data Services

Abstract: We have come to a stage when information technology (IT) innovations have permeated every walk of life. Many new technologies can be used for many different purposes and in different contexts other than the workplace. The current study attempts to understand individual adoption of IT innovations that are used beyond work settings. We define a new class of IT innovations called multipurpose information appliances, which are personal, universally accessible, and multipurpose. The ubiquitous nature of these appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
345
1
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 505 publications
(362 citation statements)
references
References 54 publications
12
345
1
4
Order By: Relevance
“…In conclusion, as prior research demonstrates, we find that innovativeness is significant in using ubiquitous computing services in urban environments. On the other hand, perceived enjoyment represents an intrinsic motivation, and several previous researchers have found a significant role of it in intention toward MDS [21,23,27,30,31,39]. In fact, in accordance with our study, Kim et al [30] Karahanna, and Straub [83] noted that understanding the role of perceived enjoyment over time is an important avenue of research to pursue.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In conclusion, as prior research demonstrates, we find that innovativeness is significant in using ubiquitous computing services in urban environments. On the other hand, perceived enjoyment represents an intrinsic motivation, and several previous researchers have found a significant role of it in intention toward MDS [21,23,27,30,31,39]. In fact, in accordance with our study, Kim et al [30] Karahanna, and Straub [83] noted that understanding the role of perceived enjoyment over time is an important avenue of research to pursue.…”
Section: Discussionsupporting
confidence: 90%
“…Previous works have shown that, as theorized in the original TAM, perceived usefulness has both a direct effect and an indirect effect via ease of use on intention to use [21,23,27,53]. In addition, the Van der Heijden's model [24] provides some evidence that it has an indirect impact on intention to use through perceived ease of use as well as perceived enjoyment.…”
Section: Research Model and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers should have reasonable validations behind their selection of a specific theory [32], mainly through rigorous justifications of why and how the selected theory fits in the context in which it is applied, and how it would be tied to the specific needs and aims of the research [31]. This is especially relevant in e-Participation context, where the majority of research works are widely criticized due to the lack of clear explanations of how the used theories were selected [23,35,55].…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…In addition, users who have strong attachment feel that they can emphasized on self-projection which leads to production of satisfaction (Belk, 1988). As a result, the current device that produces high perceived value will produce higher satisfaction and higher chances of continuous usage (Hong et al, 2006). Furthermore, the expectation theory that matches the users in performing a certain task, which expectation and termination of that task and the results obtained by comparing the value for the recognition of the value will be different.…”
Section: Attachmentmentioning
confidence: 99%